The Coaches’ Perceptions and Experience Implementing a Long-Term Athletic Development Model in Competitive Swimming - Costa, Mário J.; Marinho, Daniel A.; Santos, Catarina C.; Quinta-Nova, Luís; Costa, Aldo M.; Silva, António J.; Barbosa, Tiago M. (Frontiers in Psychology, 2021)
The aim of this study was to analyze the association between coaches’ experience and their perceptions on the implementation of a long-term athletic development (LTAD) model created in 2016 by the Portuguese Swimming Federation. Eighty-six swimming coaches were assembled in groups according to their experience level: “novice” (n = 24), “intermediate” (n = 26) and “experienced” (n = 36) and answered a questionnaire with the following items: (i) the awareness of the existing model; (ii) the acceptance; (iii) the usefulness; and (iv) the implementation of this model. Regardless of experience, ~67% of the coaches were aware of the model. Among those, a large number showed acceptance (~97%) and confidence in its usefulness (~83%) for their daily practice. Most coaches showed concerns about the fact that their peers do not respect the model frameworks, declaring the search for their swimmers’ immediate success (~58%) as the main cause for such behavior. Results also showed an association between experience and the knowledge about the model existence (χ2 (2) = 10.223, p < 0.01, V = 0.345), and experienced coaches exhibited better knowledge than their intermediate (χ2 (2) = 9.555, p < 0.01, V = 0.393) or novice (χ2 (2) = 5.926, p = 0.02, V = 0.314) counterparts. While there was an association between the coaches’ experience and the knowledge about the LTAD model existence, this situation seems not to influence the way coaches accept and understand the usefulness of the model for their daily practice.